2015
DOI: 10.1089/dia.2014.0343
|View full text |Cite
|
Sign up to set email alerts
|

Taking a Closer Look—Continuous Glucose Monitoring in Non-Critically Ill Hospitalized Patients with Type 2 Diabetes Mellitus Under Basal-Bolus Insulin Therapy

Abstract: Our data exhibit a good agreement between overall CGM and BG measurements, but there were a high number of missed hypo- and hyperglycemic episodes with BG measurements, particularly during nighttime. Overall assessment of glycemic control using CGM is feasible, whereas the use of CGM for individualized therapy decisions needs further improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 30 publications
3
33
1
2
Order By: Relevance
“…First of all, the study was a single‐arm study without a direct comparator, as the primary purpose was to show that the GlucoTab algorithm can be used without modifications in combination with insulin glargine U300. The sample size was rather small as previous studies have indicated that 15 to 30 patients can provide deep insight into 24‐hour glycaemia when using CGM . Furthermore, this trial was performed in an endocrinology ward with highly experienced staff that was already familiar with GlucoTab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, the study was a single‐arm study without a direct comparator, as the primary purpose was to show that the GlucoTab algorithm can be used without modifications in combination with insulin glargine U300. The sample size was rather small as previous studies have indicated that 15 to 30 patients can provide deep insight into 24‐hour glycaemia when using CGM . Furthermore, this trial was performed in an endocrinology ward with highly experienced staff that was already familiar with GlucoTab.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was rather small as previous studies have indicated that 15 to 30 patients can provide deep insight into 24-hour glycaemia when using CGM. 10,12,38 Furthermore, this trial was performed in an endocrinology ward with highly experienced staff that was already familiar with GlucoTab. In summary, basal-bolus insulin therapy using GlucoTab in combination with insulin glargine U300 can be safe and efficacious without an increase in hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies comparing POC-GM and CGM in hospitalized patients have highlighted the benefits of the latter in general ward settings [66]. Schaupp et al [67] applied blinded CGM to 84 hospitalized patients with Type 2 diabetes in a general ward, and retrospectively compared CGM values with four-daily POC-GM measurements over a period of 501 patient-days. The authors reported that the number of nocturnal hypoglycaemic episodes (<3.9 mmol/l) detected by CGM was 15-fold higher than the number detected by POC-GM.…”
Section: Continuous Glucose Monitoringmentioning
confidence: 99%
“…In this issue of Diabetes Technology & Therapeutics, Schaupp et al 9 present results from use of professional CGM in 84 hospitalized non-critically ill subjects undergoing insulin titration. They identified a large number of undetected hypoglycemic events, particularly overnight, and a substantial number of hyperglycemic events, most commonly between 6 a.m. to noon.…”
Section: Evidence For Inpatient Cgmmentioning
confidence: 99%